Coordination of cell organelles to promote metabolon formation - Zhou Sha; Anthony M. Pedley; Timothy D. Iles; Shaoqing Zhang; Jack R. Staub; Ruobo Zhou; Stephen J. Benkovic (Proceedings of the National Academy of Sciences, 2026)
The spatial coordination between cellular organelles and metabolic enzyme assemblies represents a fundamental mechanism for maintaining metabolic efficiency under stress. While previous work has shown that membrane-bound organelles regulate metabolic activities and that membrane-less condensates conduct metabolic reactions, the coordination between these two organizations remains unaddressed. By using a combination of proximity labeling, superresolution fluorescence microscopy, and metabolite analyses using isotopic tracing, we investigated the relationships between these metabolic hotspots. Here, we show that nutrient deficiency elongates mitochondria and transforms the ER from a tubular to sheet-like morphology, coinciding with increased mitochondrial respiration and inosine 5′-monophosphate levels. These structural changes promote the colocalization of purinosomes with these organelles, enhancing metabolic channeling. Disruption of ER sheet formation via MTM1 knockout destabilizes purinosomes, impairs substrate channeling, and reduces intracellular purine nucleotide pools without altering enzyme expression. Our findings reveal that organelle morphology and interorganelle contacts dynamically regulate the assembly and function of metabolic condensates, providing a structural basis for coordinated metabolic control in response to nutrient availability.